Studi Literatur : Potensi dan Pengembangan Energi Angin sebagai Sumber Energi Baru Terbarukan di Wilayah Gorontalo - Sudarmanto Hasan; Fitryane Lihawa; Dewi Wahyuni K. Baderan (JURNAL WILAYAH, KOTA DAN LINGKUNGAN BERKELANJUTAN, 2024)
This study aims to analyze the potential for developing Wind Power Plants (PLTB) in Gorontalo Province, focusing on wind speed in several strategic locations. The consistent and relatively high wind speeds in coastal and lowland areas of Gorontalo make the region highly suitable for developing wind energy as a renewable energy source. This research utilizes meteorological data to measure wind speed at four locations: Batudaa Pantai 1, Batudaa Pantai 2, Kwandang, and Sumalata. The analysis reveals that wind speeds range from 6.73 m/s to 7.08 m/s, with electricity generation capacity per turbine ranging from 146 kW to 170 kW. The total electricity capacity that can be generated by 30 turbines across these locations is 18.9 MW. This potential provides a significant contribution to meeting renewable energy needs in Gorontalo and Indonesia in general. However, the development of PLTB in this area requires further consideration of technical, economic, social, and regulatory aspects. Therefore, it is recommended to conduct a comprehensive feasibility study to assess the technical and economic viability, as well as the social and economic impacts on local communities. Additionally, government support in terms of policy and fiscal incentives will expedite the development of PLTB in Gorontalo, which in turn can contribute to reducing greenhouse gas emissions and supporting sustainable energy in the future.